An integrative action research paper (IAR) on improving interpersonal relationships among employees of ABC Furniture Store - Lao, Jasmine O. (Animo Repository, 2020)
This action research focused on improving weak interpersonal relationships as well as increasing the low level of communication in the workplace. Neglecting of these issues resulted in (1) increased employee friction and conflicts (2) low coordination and teamwork (3) increased workplace inefficiencies and errors. The company, ABC Furniture Store is a small retail enterprise located along A. Mabini, Caloocan City. The action researcher is currently working as the store manager of the company. Main responsibilities consist of overseeing store operations, performing human resource and finance functions. The store owner together with all employees shared vital information and collaborated with the action researcher in the whole process of the research project. This research was guided by the theoretical and conceptual framework namely, Social Penetration Theory and ADKAR’s Change Management Model. As a result, the following interventions were made: (1) Annual team-building activity (2) Monthly town-hall meeting. With management interventions on promoting a positive workplace atmosphere together with the increased level of interaction and face to face dialogues, interpersonal relationships among employees were strengthen. Now, there is less employee friction and conflicts. Rather than focusing on their task, everyone is working towards a common goal. As a team, employees were able to formulate new strategies and policies.